Unthinking remembrance? Blood Swept Lands and Seas of Red and the significance of centenaries. Issue 2 (15th March 2018) - Kidd, Jenny; Sayner, Joanne
ABSTRACT: On 4 August 2014, the now iconic evolving work by Paul Cummins and Tom Piper, Blood Swept Lands and Seas of Red, opened at the Tower of London. Each of the 888, 246 poppies in the Tower's moat represented one British life lost in the First World War (FWW). This article uses a unique dataset of 1488 responses to the installation in order to probe the impacts of this high profile intervention. Systematic analysis of that data allows us to explore the centenary as a catalyst for remembrance activity, focusing on the kinds of "unthinking remembrance" that our research made visible. We detail how visitor responses activated a series of familiar tropes about past conflict, which often neglected recent work that has attempted to diversify perspectives about the past. This calls into question the extent to which policy objectives associated with pluralising narratives about the FWW during this centenary had been successful at this early stage in the commemoration and are likely to be successful in the future. As the "cult of the centenary" becomes ever more embedded within education and policy frameworks, and refracted within the programming of national media and cultural organisations, we contend that much can be learned about how to usefully frame commemorative activities from the unprecedented case of Blood Swept Lands and Seas of Red .